Proceedings of SPE/ICoTA Coiled Tubing Conference &Amp; Exhibition 2006
DOI: 10.2523/99596-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Bit Hydraulics Model for Gasified Drilling Fluids

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractDetermination of pressure drop at the bit is one of the major concerns for establishing proper hydraulic design. Little has been known about pressure drop estimation at the bit for single phase muds, and even less is known about gasified fluids. The aim of this study is to fulfill this gap in the literature. Although there are numerous studies on this subject available in the literature, they are either valid for high gas flow rates or developed using very st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Researchers at the beginning of modern industry have noted this phenomenon and found that have many applications as what is applied in energy production, materials factories producing and chemical factories. Dogen et al (2006) [2] presented a study of the theory to calculate pressure drop losses for multiple phases of fluids through the use of a mathematical model that was developed using account program works at the expense of losses through nozzle flux area. Results obtained compared with the results of other models were found less than 10%.…”
mentioning
confidence: 99%
“…Researchers at the beginning of modern industry have noted this phenomenon and found that have many applications as what is applied in energy production, materials factories producing and chemical factories. Dogen et al (2006) [2] presented a study of the theory to calculate pressure drop losses for multiple phases of fluids through the use of a mathematical model that was developed using account program works at the expense of losses through nozzle flux area. Results obtained compared with the results of other models were found less than 10%.…”
mentioning
confidence: 99%